2011
DOI: 10.1016/j.ejcts.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of depressive and anxiety symptoms 8 years after coronary artery bypass grafting

Abstract: Depressive and anxiety symptoms occurred in many cardiosurgical patients before and after CABG. Good results of the surgical procedure did not cause reduction of depressive symptoms. Anxiety symptoms were much more common perioperatively than depressive ones and decreased significantly after surgery. Preoperative assessment of depressive and anxiety symptoms can indicate the risk group and suggest care proceedings during the rehabilitation period to improve the effectiveness of surgical coronary revascularizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
(38 reference statements)
5
12
0
Order By: Relevance
“…initial minor depression are the patients with the greatest decrease in symptoms by 12 months after surgery, those with major depression demonstrate a stability in their level of distress over the entire follow-up period. The relative stability of trajectories over time is consistent with a study that found relatively unchanged levels of depression and anxiety 8 years after CABG (Kustrzycki et al, 2012). In terms of anxiety trajectories, results showed that patients experience a decrease in anxiety symptoms over the first 12 months, but this decrease was only significant for patients in the remitted minor anxiety.…”
Section: Stability Of Symptom Trajectories: Greatest Improvements By supporting
confidence: 88%
See 1 more Smart Citation
“…initial minor depression are the patients with the greatest decrease in symptoms by 12 months after surgery, those with major depression demonstrate a stability in their level of distress over the entire follow-up period. The relative stability of trajectories over time is consistent with a study that found relatively unchanged levels of depression and anxiety 8 years after CABG (Kustrzycki et al, 2012). In terms of anxiety trajectories, results showed that patients experience a decrease in anxiety symptoms over the first 12 months, but this decrease was only significant for patients in the remitted minor anxiety.…”
Section: Stability Of Symptom Trajectories: Greatest Improvements By supporting
confidence: 88%
“…The relative stability of trajectories over time is consistent with a study that found relatively unchanged levels of depression and anxiety 8 years after CABG (Kustrzycki et al, 2012). The relative stability of trajectories over time is consistent with a study that found relatively unchanged levels of depression and anxiety 8 years after CABG (Kustrzycki et al, 2012).…”
Section: Stability Of Symptom Trajectories: Greatest Improvements By supporting
confidence: 86%
“…They also found that major depressive disorder increased the frequency of cardiac events independent of the usual risk factors [15]. These findings suggest that a surgically successful cardiac operation does not always correlate with the improvement of individual life expectancies after surgery [2] and does not decrease level of depressive symptoms [21]. …”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] The presence of anxiety and/or depression before surgery has the effect on cardiac rehabilitation outcomes after surgery, and both the factors are triggered and contributed using stress levels; hence, there is a need for early diagnosis and supportive therapeutics that involve mind–body interventions. [ 13 ] There is need for interventions which target stress management[ 14 ] and improve QOL, in particular after CABG. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%